PENGARUH PENGELUARAN PEMERINTAH TERHADAP INVESTASI DAERAH SUMATERA UTARA - ENNI SARI SIREGAR (Institut Pendidikan Tapanuli Selatan, 2016)
This article focused on analyze effect of the goverment expenditure to investment in North Sumatera. Data used time series of 1982-2012. This article use analyzer model equation with method of analysis using the correlation formula